Exploring the role of internal social media in fostering employee green behavior (EGB) - Peggy M.L. Ng; Tai Ming Wut; Jason K.Y. Chan; Mei Mei Lau; Cherry T.Y. Cheung; Man Lung Jonathan Kwok; Ellesmere T.K. Choy (Sustainable Futures)
Previous research has consistently highlighted the impact of internal communication strategies on employees’ pro-environmental behavior. However, the effect of internal social media on employee green behavior (EGB) and its underlying relationships remains unclear. This study examined green communication strategies used by organizations to encourage EGB on internal social media. Based on two experimental studies, the current research investigated the effect of internal social media post on EGB, and the interplay between message framing and construal levels to evaluate how framed messages of internal social media post trigger employees’ self-efficacy in promoting EGB. Study 1 revealed that internal social media messages could effectively encourage employees’ self-efficacy and further generate EGB. Following the results of study 1, study 2 revealed that loss-framed messages paired with a concrete condition on internal social media effectively induce employees’ self-efficacy and encourage EGB. The results demonstrated that the most effective communication strategy for delivering green messages on internal social media is to induce employees’ self-efficacy. Social media messages can inspire employees who do not currently engage in EGB to take action and adopt green practices. Thus, marketing managers of the organizations can create novel framed internal social media posts to encourage employees to engage in EGB.